Evaluating the Impact of Blended Learning in Clinical Pharmacology Among Medical and Allied Health Undergraduates: A Cross-Sectional Study - Ye, Beibei; Huang, Lanjie; Peng, Keyi; Liu, Yang; Chen, Xin; Li, Bingliang; Li, Ji; Yang, Jian (Journal of Basic and Applied Pharmacology, 2024)
Objective: This study evaluated the effectiveness of a blended learning model in teaching clinical pharmacology to undergraduate healthcare students, including those from medical and allied health disciplines. The study assessed the model’s impact on their career development and examined its effects on academic performance, knowledge retention, practical application of pharmacological concepts, career aspirations, and clinical practice readiness. Methods: A cross-sectional survey was conducted from April 10 to May 20, 2024, in China. Undergraduate healthcare students who completed a clinical pharmacology course via blended learning participated. Data were collected using an online questionnaire through “Questionnaire Star”. Out of 513 collected questionnaires, 330 valid responses were analyzed using IBM SPSS Statistics and Python for descriptive statistics, correlation, regression, and cluster analyses. Results: The blended learning model significantly enhanced student engagement and knowledge acquisition. The Flipped Classroom was the most frequently used method (average frequency 0.75), followed by Face-to-Face Teaching (0.71) and Online MOOC Learning (0.68). Both male and female students reported similar knowledge impact (4.08±0.93 for males, 4.00±0.90 for females). Clinical Medicine students reported the highest satisfaction (4.44±0.66). Regression analysis identified Online MOOC Learning (0.260) and Face-to-Face Teaching (0.201) as significant predictors of knowledge acquisition. Cluster analysis revealed three distinct student groups with varying satisfaction and perceived effectiveness. Objective: This study evaluated the effectiveness of a blended learning model in teaching clinical pharmacology to undergraduate healthcare students, including those from medical and allied health disciplines. The study assessed the model’s impact on their career development and examined its effects on academic performance, knowledge retention, practical application of pharmacological concepts, career aspirations, and clinical practice readiness. Methods: A cross-sectional survey was conducted from April 10 to May 20, 2024, in China. Undergraduate healthcare students who completed a clinical pharmacology course via blended learning participated. Data were collected using an online questionnaire through “Questionnaire Star”. Out of 513 collected questionnaires, 330 valid responses were analyzed using IBM SPSS Statistics and Python for descriptive statistics, correlation, regression, and cluster analyses. Results: The blended learning model significantly enhanced student engagement and knowledge acquisition. The Flipped Classroom was the most frequently used method (average frequency 0.75), followed by Face-to-Face Teaching (0.71) and Online MOOC Learning (0.68). Both male and female students reported similar knowledge impact (4.08±0.93 for males, 4.00±0.90 for females). Clinical Medicine students reported the highest satisfaction (4.44±0.66). Regression analysis identified Online MOOC Learning (0.260) and Face-to-Face Teaching (0.201) as significant predictors of knowledge acquisition. Cluster analysis revealed three distinct student groups with varying satisfaction and perceived effectiveness. Conclusion: The blended learning model effectively enhances academic performance, knowledge retention, and professional skills among undergraduate medical and allied health students. A balanced integration of online and offline components maximizes learning outcomes. Tailored approaches are needed for different disciplines. Future research should focus on longitudinal studies to assess the long-term impact on career development.